Strategies for Improving the Utilization of E-Learning in the Teaching and Learning of Accounting - Jacinta Ifeoma Obidile (Journal of Vocational Education Studies, 2023)
The electronic learning (e-learning) as a mode of teaching and learning has come to stay in the history of tertiary institutions in Nigeria, but due to several challenges confronting its technological operations in the country, e-learning is yet to be fully implemented in the teaching and learning processes in Nigeria, including the teaching and learning of accounting. This study therefore ascertained the strategies that could be used to improve the utilization of e-learning in the teaching and learning of accounting. Census survey research design was used for the study. A total of 116 final year accounting students made up of 62 males and 54 females were used. A questionnaire which was validated by three experts with a reliability coefficient of 0.76 was the instrument for data collection. Data collected were analysed using mean and standard deviation for the research questions and z-test for the hypotheses. Findings revealed that; provision of adequate IT support, provision of well-equipped ICT centre in every tertiary institution, provision of IT standard for implementation, among others were strategies for improving the utilization of e-learning. Also, there was no significant difference in the mean ratings of the respondents on the strategies that could be used to enhance the utilization of e-learning in the teaching and learning of accounting as a result of gender. Recommendations were also proffered.